Ultra-processed foods: a fit-for-purpose concept for nutrition policy activities to tackle unhealthy and unsustainable diets - Mark Lawrence (Cambridge University Press, 2023)
Modern nutrition science began approximately 100 years ago in the context of nutrient deficiency diseases. Nutrition research and policy activities were framed mostly within a reductionist paradigm in which foods were analysed as being a collection of their constituent nutrients. Today, nutrition problems extend to all forms of malnutrition as well as environmental sustainability considerations and are associated with food and dietary pattern exposures. In 2009, researchers investigating the nutrition transition in Brazil proposed that industrial food processing was a key determinant of nutrition problems. The NOVA food classification system which is based on the nature, extent and purposes of food processing was developed to operationalise this proposition. The ultra-processed food (UPF) concept within NOVA is receiving much attention in relation to nutrition research and policy activities. This commentary describes the UPF concept as being fit-for-purpose in providing guidance to inform policy activities to tackle unhealthy and unsustainable diets. There is now a substantial body of evidence linking UPF exposure with adverse population and planetary health outcomes. The UPF concept is increasingly being used in the development of food-based dietary guidelines and nutrition policy actions. It challenges many conventional nutrition research and policy activities as well as the political economy of the industrial food system. Inevitably, there are politicised debates associated with UPF and it is apparent a disproportionate number of articles claiming the concept is controversial originate from a small number of researchers with declared associations with UPF manufacturers. Prominent examples of these claims are assessed.